Mass spectral studies on 1‐n‐pentyl‐3‐(1‐naphthoyl)indole (JWH‐018), three deuterium‐labeled analogues and the inverse isomer 1‐naphthoyl‐3‐n‐pentylindole. (26th March 2015) - Thaxton, Amber; Belal, Tarek S.; Smith, Forrest; DeRuiter, Jack; Abdel‐Hay, Karim M.; Clark, C. Randall
Abstract : Rationale: A number of synthetic cannabinoids such as the 1‐alkyl‐3‐acylindoles are the target of significant designer drug activity. One of the first waves of these compounds identified in clandestine samples was 1‐n‐pentyl‐3‐(1‐naphthoyl)indole, JWH‐018. These totally synthetic molecules can be prepared in a number of regioisomeric forms. Methods: The electron ionization mass spectrometric (EI‐MS) fragmentation of the 1‐n‐pentyl‐3‐(1‐naphthoyl)indole is compared to its inverse isomer 1‐naphthoyl‐3‐n‐pentylindole. These two substances are directly available from indole using identical precursor reagents and similar reaction conditions. Stable isotope deuterium labeling of the three major regions of the JWH‐018 molecule allows confirmation of the structures of the major fragment ions. The spectra for the 1‐n‐pentyl‐3‐(1‐naphthoyl)‐d5 ‐indole, 1‐n‐pentyl‐3‐(1‐d7 ‐naphthoyl)indole and 1‐d11 ‐n‐pentyl‐3‐(1‐naphthoyl)indole provide significant assistance in elucidating the structures for the major fragment ions in JWH‐018. Results: The EI mass spectra for these isomers show a number of unique ions which allow for the differentiation of the 1‐alkyl‐3‐acylindole compounds from the inverse regioisomeric 1‐acyl‐3‐alkylindoles. The fragment ion [M–17] + at m/z 324 for JWH‐018 was formed by the elimination of a hydroxyl radical and the spectra of the three deuterium‐labeled derivatives indicated the loss of hydrogen from the naphthalene ring. Further structural analogues suggest the hydrogen to come from the 8‐position of the naphthalene ring. Conclusions: The three deuterium‐labeled analogues provide significant assistance in confirming the structures for the major fragment ions in the mass spectrum of the traditional synthetic cannabinoid compound, 1‐n‐pentyl‐3‐(1‐naphthoyl)indole, JWH‐018. The 1‐naphthoyl‐3‐n‐pentylindole inverse regioisomer can be easily differentiated from the traditional synthetic cannabinoid compound. Copyright © 2015 John Wiley & Sons, Ltd.